A proposed accounting model for evaluating the performance of Islamic banks according to accounting and Sharia standards - Iraqi Islamic banks as a model - Talal Mohammed Ali Aljajawy,; Mustafa Salam Al-Dfaey, (Iraqi Journal for Administrative Sciences, 2025)
a) The Islamic banking industry becomes one of the most important economic pillars of economies Islamic countries , that was because of the achievements of the industry growth during the period of four decades past , as the number of Islamic banking , according to the latest statistics to more than 450 bank and institutions in different countries . this is because development and progress witnessed in the industry to factors liberation witnessed by Islamic countries and desire of Muslim communities seeking banking alternative appropriate to the realities of social , religious and economic away from banking systems traditional menu , and in light of these important the Iraqi Islamic banks like other financial institutions Iraqi inches in banking environment characterized complex resulting from the problems and successive experienced by the country in recent All this born negative impact reflected on the performance of Iraqi Islamic banks dramatically demonstrated by the oscillation happening in their performance over the past four years , and despite the fact that the Islamic banking industry nascent as it does not go its inception ten years and therefore they need more time to overcome these crises as the lack of openness to others and the formation of real companies with Islamic financial institutions regional or international made Iraqi banks Islamic banks lagging behind global , came this study in an attempt to shed light on Iraqi Islamic banks and identify performance to highlight the economic role they play in the economic development process through their existing possibilities of material and technical , as well as highlight the role of the observer forensic leading from the Bodies internal legitimacy and explain the role and the importance of supreme regulatory bodies legitimacy which is the resident to perform bodies internal legitimacy of Islamic banking through submitted these bodies of standards legitimacy promised as one of the most important regulators tools to detect deviations occurring in the performance of Islamic banks as well as the upgrading of reality accounting for Islamic banks of Iraqi through the assessment of their performance in light of the accounting standards of legitimacy , the researcher reached to the conclusion that Iraqi Islamic banks need to develop their tools technical and financial consistent with reality of economic and financial and research for new investment tools to enable them to improve their performance as well as the need to comply with legitimacy standards which prevent into legitimacy for being longer tool and means to ensure that the Islamic bank to reach the best performance and the achievement principle of legitimacy regulate